(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In this paper, a new approach is being proposed to achieve mutual exclusion in distributed system usingÂ computer network and topology of nth nodes. In this executive approach nodes communicate amongÂ themselves using message passing technique. In this executive approach, distributed system with nÂ nodes is logically partitioned into number of sub distributed system having only mÂ½ nodes, where m isÂ obtained by adding a minimum number in n to make it next perfect square number only if n is not aÂ perfect square. Proposed algorithm is a Token based approach and achieves token optimally in 2Â messages only for the best case and in worst case a node achieves token in n messages only.